40 Years of the APOC Partnership - Roungou, Jean-Baptist (Public Library of Science, 2015)
The fight against onchocerciasis (river blindness), one of the most devastating neglected tropical diseases (NTDs), has mobilized significant resources and brought together diverse public and private stakeholders. Affected communities, governments of endemic countries, non-governmental development organizations (NGDOs), donors, and researchers are contributing, each in their own way, to what is considered today as one of the major public health achievements of recent decades in Africa. Onchocerciasis is losing ground, and its elimination in Africa is now possible within a reasonable timeframe.